Modal Sosial Guru dan Dampaknya terhadap Partisipasi Orang Tua dalam Pendidikan di Komunitas Urban - Ahmad Fauzi Maulana; Hafiz Rio Wardana; Gusmaneli . (CV. ITTC INDONESIA, 2025)
Teacher social capital plays a strategic role in building collaborative relationships between schools and families, particularly in urban environments characterized by diverse social characteristics and high community mobility. This study examines the concept of teacher social capital, the challenges faced in urban contexts, and its impact on parental participation in education. Social capital is understood as a teacher's relational capabilities, encompassing social networks, trust, norms, values, and communication skills that enable effective collaboration. Various studies indicate that challenges such as social heterogeneity, parental busyness, limited digital literacy, and a weak culture of participation can hinder the formation of stable school-family relationships. Literature findings reveal that teacher social capital significantly influences the quality of two-way communication, support for home learning, and school legitimacy in the eyes of parents. This study also highlights the importance of strategies to strengthen social capital through communication training, collaborative programs, technology utilization, optimization of school committees, and institutional support. By strengthening teacher social capital, parental involvement can increase, thereby making the educational process in urban areas more effective and sustainable.